2008
DOI: 10.1007/s10620-008-0452-2
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Hypoxemia During Ambulatory Gastrointestinal Endoscopy in ASA I–II Patients

Abstract: In ASA I and II patients, BMI significantly correlated with the number of hypoxemic episodes, whereas age >or= 60 years and meperidine dose were significant risk factors for hypoxemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
69
3
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 25 publications
4
69
3
1
Order By: Relevance
“…This study is important in highlighting the fact that the doses of propofol were reduced by almost 50% in association with only 1 mg of midazolam. Compared with the Australian study (Qadeer et al, 2009) the doses of fentanyl and midazolam were notably lower compared with higher doses in using propofol alone. In interpreting the Indiana trial one must take into account that in the study only a small number of patients (200 in total) were included.…”
Section: Positive Effects Negative Effectscontrasting
confidence: 55%
See 2 more Smart Citations
“…This study is important in highlighting the fact that the doses of propofol were reduced by almost 50% in association with only 1 mg of midazolam. Compared with the Australian study (Qadeer et al, 2009) the doses of fentanyl and midazolam were notably lower compared with higher doses in using propofol alone. In interpreting the Indiana trial one must take into account that in the study only a small number of patients (200 in total) were included.…”
Section: Positive Effects Negative Effectscontrasting
confidence: 55%
“…In terms of approaching the "combination" scheme, an Australian study reported median total doses of 4 mg midazolam, 75 mg fentanyl and 60 mg propofol in a sample of 500 cases from a total of 28,472 patients undergoing ambulatory endoscopy. In all patients the three drugs were used (Qadeer et al, 2009). In a Swiss study (Kulling et al, 2007) that included 27,061 patients undergoing ambulatory endoscopy, propofol was used as single agent for sedation.…”
Section: Positive Effects Negative Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypoxemia has been shown to trigger myocardial ischemia during endoscopy in individuals with and without previous cardiac history and can eventually lead to neurological damage and death [21,22,23]. Due to the intuitive and straight relation between hypoxemia and adverse events as well as the rarity of severe complications during endoscopy, hypoxemia has been used as a surrogate for main periprocedural cardiopulmonary events [24,25]. …”
Section: Introductionmentioning
confidence: 99%
“…However, for moderate sedation in left lateral position, unrecognized sleep apnea [59] did not appear to predict transient hypoxia or AEs in one routine endoscopy study [37]; another study found that BMI in ASA I-II patients predicted the number of hypoxemic episodes [43]. Increased BMI and obstructive sleep apnea can predict perioperative morbidity after surgery [60] and may increase risk and make airway maintenance more difficult in deep sedation [42], especially for the semiprone positioning that is standard for ERCP.…”
Section: Case Context and Comorbidity Quantificationmentioning
confidence: 99%